Two-Year Results of Think Health! ¡Vive Saludable! - A Primary Care Weight Management Trial - Kumanyika, Shiriki K. (Obesity (Silver Spring), 2018)
OBJECTIVE: Think Health! ¡Vive Saludable! evaluated a moderate-intensity lifestyle behavioral weight loss program in primary care over 2 years of treatment. Final analyses examined weight change trajectories by treatment group and attendance. METHODS: Adult primary care patients (n=261; 84% female; 65% black; 16% Hispanic) were randomly assigned to Basic Plus (moderate-intensity; counseling by primary care clinician and a lifestyle coach) or (Basic; clinician counseling only). Intent-to-treat analyses used all available weight measurements from data collection, treatment, and routine clinical visits. Linear mixed-effects regression models adjusted for treatment site, gender, and age, and sensitivity analyses evaluated treatment attendance and the impact of loss to follow up. RESULTS: Model-based estimates for 24-month weight change from baseline were mean [95% CI] −1.34 kg [−2.92, 0.24] in Basic Plus and −1.16 kg [−2.70, 0.37] in Basic (net difference − 0.18 kg [−2.38, 2.03] p=0.874). Larger initial weight loss in Basic Plus was attenuated by a ~0.5 kg rebound at 12-to-16 months. Each additional coaching visit was associated with a 0.37 kg greater estimated 24-month weight loss (p=0.01). CONCLUSIONS: These findings in mostly black and Hispanic female primary care patients suggest that strategies to improve treatment attendance may improve weight loss resulting from moderate-intensity counseling.